Fermentation of Sugarcane Sludge to Improve Dry- and and Organic Matters Digestibility and Rumen Parameters In Vitro - Widodo, y; Muhtarudin, Muhtarudin (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2008)
The objective of the research was to study the utilization of fungi and yeast on sugarcane sludge fermentation. The treatments of the first experiment were P0= sugarcane sludge without fermentation; P1= fermentation by Saccharomyces cereviceae; P2 = fermentation by Aspergillus oryzae; P3 = fermentation by Aspergillus niger; P4= fermentation by Rhizopus orryzae. Treatments were arranged in a Completely Randomised Design. The treatments of the second experiments were R0 = basic rations, R1 = R0 + 5% fermented of sugarcane sludge, R2 = R0 + 10% fermented of sugarcane sludge, R3 = R0 + 15% fermented of sugarcane sludge, R4 = R0 + 20% fermented of sugarcane sludge. Treatments have significant effects (P<0.05) on VFA and NH3 parameters. Based on these parameters, fermentation of sugarcane sludge using Saccharomyces cereviceae had better results compared to others. The treatments had significant effect (P<0.05) on NH3, and based on polynomial orthogonal test the treatments had linear curve of Y= 4,035 +0,237X. However, treatments had no significant effects on VFA and organic matters digestibility. The dry matters digestibility parameters were significantly affected (P<0.05), and the curve response was linear with equation of Y=45,964 - 0,294X. (Animal Production 10(1): 30-33 (2008) Key Words: Sugarcane sludge processing, fungi, yeast, in vitro